An alternative approach to estimation of the probability of default for commercial entities: The modified KMV Merton model - Andrew Kioi Njeru (Kenya Bankers Association (KBA), 2019)
We carry out an empirical test of KMV model for using private companies that are not listed on a stock exchange and in doing so, substitute book values for market values and fluctuations of bank account balances for volatility of stock prices. This study reveals a surprising effectiveness of the KMV model and its applicability for estimating probability of default for companies that are not listed on a stock exchange but only with a modification to adopt the actual observed asset growth of the company reported in the books of accounts instead of using the risk-free rate. The adoption of the bank balances as a proxy for the asset volatility has also performed well. One other finding is that the only three companies that had material exposure and defaulted did not have the up-to-date audited books of accounts. We could therefore not test the effectiveness of the KMV model because the three had no up to date books of accounts. This makes one to conclude that absence of audited book of accounts for a significant borrower is a major negative signal that a company is likely to default. This is more significant for larger companies who have a legal requirement to prepare the audited financial statements and the absence may be inferred to as a signal of inability to conclude the closure books of accounts with external auditors due to doubts about going concern.
Keywords: 330; Spillover; Commercial banks; BVAR; Shocks; Volatility